2012
DOI: 10.1158/1078-0432.ccr-12-0181
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Phase II Study of Single-Agent Enzastaurin in Previously Treated Waldenström Macroglobulinemia

Abstract: Purpose: Enzastaurin is a serine/threonine kinase inhibitor that showed antiangiogenic, antiproliferative, and proapoptotic properties in vitro and antitumor activity in vivo in a xenograft Waldenstr€ om macroglobulinemia (WM) model. These findings provided the rationale for a multicenter phase II trial of oral enzastaurin in previously treated patients with WM.Experimental design: Patients who were treated with 1 to 5 prior regimens and who had a baseline immunoglobulin M level 2 times or more the upper limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Enzastaurin is an investigational oral serine/threonine kinase inhibitor that targets the PKC and PI3K/AKT pathways and has been evaluated in a phase II trial of 42 patients, showing an ORR of 38% (Table 7). It was well tolerated, and grade 3 toxicities were rare with leukopenia and septic shock in 1 patient each [133]. In a recent phase III trial of diffuse large B cell lymphoma in which enzastaurin was being evaluated in a maintenance setting, the primary study end-point of disease free survival was not met, impeding its development.…”
Section: Phosphoinositide-3-kinase (Pi3k) Akt and Mammalian Target mentioning
confidence: 99%
“…Enzastaurin is an investigational oral serine/threonine kinase inhibitor that targets the PKC and PI3K/AKT pathways and has been evaluated in a phase II trial of 42 patients, showing an ORR of 38% (Table 7). It was well tolerated, and grade 3 toxicities were rare with leukopenia and septic shock in 1 patient each [133]. In a recent phase III trial of diffuse large B cell lymphoma in which enzastaurin was being evaluated in a maintenance setting, the primary study end-point of disease free survival was not met, impeding its development.…”
Section: Phosphoinositide-3-kinase (Pi3k) Akt and Mammalian Target mentioning
confidence: 99%
“…ENZ showed strong inhibitory activity in pre-clinical studies of a variety of tumors, and has been clinically tested in a wide spectrum of solid and hematological malignancies. While ENZ failed to show significant clinical benefit in solid tumors, it has showed promising results as a single agent in a variety of pretreated B-cell malignancies, including Waldenström macroglobulinemia (overall response rate (ORR) of 38.1%) [18] and follicular lymphoma (ORR of 26.4% including 2 complete responses) [19]. Targeting PKC␤ with ENZ and other novel PKC␤ inhibitors, such as AEB071, continues to be evaluated in CLL and DLBCL, in order to elucidate the exact mechanism of action, and to find the best synergistic combination [20,21] (www.clinicaltrials.gov; Identifier: NCT01854606).…”
Section: Introductionmentioning
confidence: 99%
“…Enzastaurin is an anti-angiogenic and antineoplastic agent, which acts by inhibition of PKC [50]. A multicenter Phase II study of single-agent enzastaurin in 42 patients with previously treated WM showed an ORR of 38%, with all being PR and MR [51]. A statistically significant association between response rate and IL-15 level was observed.…”
Section: Pi3k/akt/pkc Inhibitorsmentioning
confidence: 98%